Pengaruh Kapasitas Pemerintah Daerah terhadap Efektivitas Pelayanan Kesehatan Primer di Puskesmas Daerah Surabaya - Naqsya N. N, Analiya; Ashari, Khusnul Fika (VISA: Journal of Vision and Ideas, 2026)
This study aims to analyze the influence of local government capacity on the effectiveness of primary health care services at Community Health Centers (Puskesmas) in Surabaya City. This research employs a qualitative descriptive approach to obtain an in-depth understanding of institutional capacity and its role in health service delivery. Data were collected through in-depth interviews, observations, and document analysis involving officials from the Health Office, heads of Puskesmas, health workers, and service users. The findings indicate that the capacity of the Surabaya City Government reflected in human resources availability, health budget allocation, policy support, and institutional governance contributes positively to the effectiveness of primary health care services. Most service indicators show favorable performance however, variations in service quality among Puskesmas remain evident, particularly in responsiveness and managerial implementation. These differences suggest that effectiveness is influenced not only by resource availability but also by the ability to manage and implement policies consistently at the service level. In conclusion, strengthening local government capacity is essential to improving the effectiveness and equity of primary health care services, especially through enhanced human resource management, optimized budget utilization, and stronger coordination and supervision mechanisms.